Clinical Performance of Two Methods for Detecting Anti SARS-CoV-2 Antibodies - Jacobsen, Dario Gustavo (2021)
Evaluating the clinical performance of available methods to detect antibodies against Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) has become a primordial issue in clinical laboratories. The aim of this study was to evaluate the clinical performance of two methods for SARS-CoV-2 antibodies detection, an automated Chemiluminescent Immunoassay (CLIA) and an immunochromatographic Lateral-Flow Assay (LFA) in patients with positive reverse transcription polymerase chain reaction (RT-PCR). Performance for CLIA method was Positive Agreement (PA) 56.6% and Negative Agreement (NA) 96,6% for IgM and PA 85.8%/NA 90,2% for IgG. Performance for LFA method was PA 56.2% and NA 100% for IgM and PA 95.5% and NA 100 % for IgG. LFA general agreement IgG was better than CLIA. In both methods, significant differences in Kappa index are observed when IgG and IgM are compared. When evaluating the data from a clinical perspective, we found that both method performance for IgM detection may not meet the expected requirements for their clinical utility and could lead to an inappropriate medical decision. The findings of this study show that both immunoassay methods might be reliable for assessing immunological response in COVID-19 patients. Our results also confirm that IgG measurement could be helpful, especially for epidemiological studies in our population. These results provide evidence to justify epidemiological studies in our population.